A survey on building safety after completing the construction process in Malaysia using statistical approach - Zamri, Nurnadiah; Ahmad, Fadhilah; Talib, Amira Husni; Mohd Ibrahim, Mohamad Shafiq (Indonesian Society for Knowledge and Human Development (INSIGHT), 2017)
Building condition is an important issue in all over the world to enhance safety, health and sustainability of built environment. The objective of this study is to determine the most frequent causes of building failures in order to avoid the building from collapses, cracks and so on. The collection of data has been done among the engineers, workers and public. The questionnaire was distributed among engineers, contractors and public with 100 respondents. This survey focuses on two main parts of the safety which are building design and building management. The building designs are divided into four main criteria which are building structure, service design, building fitting and hazard environment. Meanwhile, the item of building management is focused on the management criteria. Results are analysed using statistical approach. Structural equation modeling (SEM) is used to evaluate the efficiency of the models’ fitness and goodness.The survey shows that all criteria are importantly needed in maintaining the safety of building after completing the contraction process.